Інформаційна підтримка управління витратами в процесі матеріально-технічного забезпечення сільськогосподарських підприємств: обліковий аспект - Саванчук, Тетяна Миколаївна; Savanchuk, Tetiana (Національний авіаційний університет, 2019)
У статті розглянуто порядок формування інформації про витрати в процесі матеріально-технічного забезпечення сільськогосподарських підприємств у їх обліковій системі. Встановлено законодавчі вимоги щодо обліку вказаних витрат та погляди науковців на зазначену проблему. Визначено основні різновиди витрат, інформація про які важлива для управління процесом матеріально-технічного забезпечення. Наведено порядок розрахунку суми витрат підприємства на організацію процесу матеріально-технічного забезпечення. Запропоновано здійснювати облік зазначених витрат на окремому рахунку та встановлено кореспонденцію рахунків з обліку досліджуваних витрат, що дало можливість окреслити основні складові інформаційної підтримки управління витратами в процесі матеріально-технічного забезпечення сільськогосподарських підприємств. The article deals with the procedure of formation of information on costs in the process of material and technical support of agricultural enterprises in their accounting system. Legislative requirements for accounting for these costs and scientists' views on the indicated problem are established. The basic types of expenses are determined, information about which is important for the management of the material and technical support process: the cost of the search and processing of information, the cost of calculating the need for relevant resources; costs of contracting; costs of opportunistic supplier behavior; costs of analytical procedures in material and technical support management; expenses related to the receipt of material and technical resources for the enterprise; costs of storage of material and technical resources and their release into production. The order of calculation of the sum of expenses of the enterprise for organization of the process of material and technical provision is given. It is proposed to record these costs on a separate account and set up the correspondence of accounts for the account of the investigated expenses. The main components of information support of cost management in the process of material and technical support of agricultural enterprises are outlined. To which it is proposed to include: implementation of the system of cost management for logistics at the enterprise, adjustment of the accounting system of the specified costs, analytical work on cost management in the process of logistics. The proposed method of accounting for these costs and analytical processing of the data, will allow management personnel of agricultural enterprises always have the information necessary to manage costs in the process of material and technical support of the enterprise.
Information support for cost management in the process of material and technical support of agricultural enterprises: accounting aspect
Keywords: витрати; costs; матеріально-технічне забезпечення; material and technical support; облік; accounting; інформація; information; рахунки; accounts; кореспонденція; correspondence; управління; management; підтримка; support